A Robust, Self‐Healable, and Shape Memory Supramolecular Hydrogel by Multiple Hydrogen Bonding Interactions. Issue 20 (3rd May 2018) - Feng, Zhanbin; Zuo, Hongli; Gao, Weisheng; Ning, Nanying; Tian, Ming; Zhang, Liqun
Abstract: A versatile double‐network (DN) hydrogel with two noncovalent crosslinked networks is synthesized by multiple hydrogen bonding (H‐bonding) interactions. The DN hydrogels are synthesized via a heating–cooling photopolymerization process by adding all reactants of agar, N ‐acryloyl glycinamide (NAGA) and N ‐benzylacrylamide (NBAA) monomers, UV initiators to a single water pot. Poly( N ‐acryloyl glycinamide‐ co ‐ N ‐benzyl acrylamide) (P(NAGA‐ co ‐NBAA)) with a triple amide in one side group is synthesized via UV‐light polymerization between NAGA and NBAA, forming a strong intermolecular H‐bonding network. Meanwhile, the intramolecular H‐bonding network is formed between P(NAGA‐ co ‐NBAA) and agars. The sol–gel phase transition of agars at 86 °C generates the molecular entanglement network. Such a double network enables the hydrogel high self‐healing efficiency (about 95%), good shape memory ability, and high mechanical strength (1.1 MPa). Additionally, the DN hydrogel is completely crosslinked by multiple hydrogen bonds (H‐bonds) and the physical crosslinking of agar without extra potential toxic chemical crosslinker. The DN hydrogels find extensive applications in the biomedical materials due to their excellent biocompatibility. Abstract : Poly( N ‐acryloyl glycinamide‐ co ‐ N ‐benzyl acrylamide)/agar double‐network hydrogels crosslinked by multiple hydrogen bonds are synthesized. The double network gives the hydrogel high self‐healing efficiency (about 95%), high mechanical strength (1.1 MPa), and good shape memory ability.